E-Learning, E-Education, and Online Training First International Conference, eLEOT 2014, Bethesda, MD, USA, September 18-20, 2014, Revised Selected Papers - Vincenti, Giovanni; Bucciero, Alberto; Vaz de Carvalho, Carlos (Lecture Notes of the Institute for Computer Sciences, Social Informatics and Telecommunications Engineering, 2014)
This book constitutes the thoroughly refereed post-conference proceedings of the First International Conference on E-Learning, E-Education, and Online Training (eLEOT 2014) held in Bethesda, MD, USA, in September 2014. The 22 revised full papers presented were carefully reviewed and selected from numerous submissions and focus topics such as web based tools, augmented reality, mobile learning, teaching frameworks and platforms, virtual learning environments.